Inhibition of transforming growth factor-β signaling in myeloid cells ameliorates aortic aneurysmal formation in Marfan syndrome - Hara, Hironori (PLoS One, 2020)
Increased transforming growth factor-β (TGF-β) signaling contributes to the pathophysiology of aortic aneurysm in Marfan syndrome (MFS). Recent reports indicate that a small but significant number of inflammatory cells are infiltrated into the aortic media and adventitia in MFS. However, little is known about the contribution of myeloid cells to aortic aneurysmal formation. In this study, we ablated the TGF-β type II receptor gene Tgfbr2 in myeloid cells of Fbn1(C1039G/+) MFS mice (Fbn1(C1039G/+);LysM-Cre/+;Tgfbr2(fl/fl) mice, hereinafter called Fbn1(C1039G/+);Tgfbr2(MyeKO)) and evaluated macrophage infiltration and TGF-β signaling in the aorta. Aneurysmal formation with fragmentation and disarray of medial elastic fibers observed in MFS mice was significantly ameliorated in Fbn1(C1039G/+);Tgfbr2(MyeKO) mice. In the aorta of Fbn1(C1039G/+);Tgfbr2(MyeKO) mice, both canonical and noncanonical TGF-β signals were attenuated and the number of infiltrated F4/80-positive macrophages was significantly reduced. In vitro, TGF-β enhanced the migration capacity of RAW264.7 macrophages. These findings suggest that TGF-β signaling in myeloid cells promotes aortic aneurysmal formation and its inhibition might be a novel therapeutic target in MFS.